Association between napping and 24-hour blood pressure variability among university students: A pilot study - Dai, Jie; Wu, Hua-ying; Jiang, Xiao-dong; Tang, Yong-jie; Tang, Hao-Kai; Meng, Li; Huang, Na; Gao, Jing-yu; Li, Jian; Baker, Julien S.; Zheng, Chan-Juan; Yang, Yi-De (Frontiers in Pediatrics, 2023)
Background Blood pressure variability (BPV) has been reported to be a predictor of cardiovascular and some cognitive diseases. However, the association between napping and BPV remains unknown. This study aimed to explore the association between napping and BPV. Materials and methods A cross-sectional study including 105 university students was conducted. Participants’ 24 h ambulatory blood pressure monitoring (24 h ABPM) were measured, and napping behaviors were investigated. BPV were measured by the 24 h ABPM, included standard deviation (SD), coefficient of variation (CV), and average real variability (ARV). Results Among the participants, 61.9% reported daytime napping. We found that nap duration was significantly associated with daytime CV of diastolic blood pressure (DBP) (r = 0.250, P = 0.010), nighttime CV of systolic blood pressure (SBP) (r = 0.217, P = 0.026), 24 h WCV of DBP (r = 0.238, P = 0.014), 24 h ARV of SBP (r = 0.246, P = 0.011) and 24 h ARV of DBP (r = 0.291, P = 0.003). Compared with the no napping group, 24 h WCV of DBP, daytime CV of DBP, and daytime SD of DBP were significantly higher in participants with napping duration >60 min. With multiple regression analysis we found that nap duration was an independent predictor for 24 h ARV of SBP (β = 0.859, 95% CI, 0.101–1.616, P = 0.027) and 24 h ARV of DBP (β = 0.674, 95% CI, 0.173–1.175, P = 0.009). Conclusions Napping durations are associated with BPV among university students. Especially those with napping durations >60 min had a significantly higher BPV than those non-nappers.